Therapeutic itinerary of hematological patients: the importance of early diagnosis (Research, Society and Development, 2022)
Objective: to identify the trajectory of patients with acute leukemia and severe aplastic anemia before the specialized care seeking care at the reference center. Methods: cross-sectional, observational, quantitative and analytical research. The research was carried out in a university hospital in the south of Brazil, in two services that care for onco-hematological patients. In the 18-month period, 237 patients were treated, according to the inclusion criteria: adults over 18 years of age, with prior treatment for education and with diagnostic confirmation, being eligible for the study, 31 patients with acute leukemia and 19 with severe aplastic anemia (n=50). Results: the median time of the search interval for help was 7 (0-158) days; diagnostic interval of 14 (0-390) days; and pre-treatment interval 2 (71-783) days. In search of care, in the first ten days after the onset of two symptoms, it occurred in 16 (61.5%) patients with acute leukemia and in 7 (41.2%) patients with severe aplastic anemia (p≥0.05). The time interval between the diagnosis, proximity to the specialized center and type of work will show statistical significance. Conclusion: the knowledge of two factors that led to the non-diagnostic delay of these actions, contributed to the understanding of health care, contributing to improve hematological assistance and the formulation of public policies, including effective strategies to improve access to specialized services.